Relevance of Macroeconomic Variables in the Indian Stock Market - Kaur, Gurloveleen (Indian Journal of Research in Capital Markets, 2016)
The study analyzed the impact of macroeconomic variables on the functioning of the Indian stock market. To achieve the research objective, monthly data of 10 macroeconomic variables, namely broad money, call money rate, crude oil price, exchange rate, foreign exchange reserve, foreign institutional investors, gross fiscal deficit, index of industrial production, inflation rate, and trade balance and one stock market index BSE 500 was used. Descriptive statistics, graphs, unit root tests, multiple regression, and Granger causality tests were employed for the study. All the variables became stationary at first difference with ADF test and PP test. This stationary data was used to find out the significant macroeconomic variables by using the multiple regression technique. One variable, that is, exchange rate was found to be significant. Granger causality test was used to check the causality relationship between the significant variable and BSE 500. It was observed that exchange rate had no relationship with closing prices of BSE 500 manufacturing firms. The study also revealed that the Indian stock market is weak form efficient because no relationship was found among the variables during the study period.